2011
DOI: 10.1270/jsbbs.61.35
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of the barley Nud gene using transgenic rice

Abstract: Most cereal crops have hulless grains (naked caryopses) with a free-threshing trait, whereas the majority of barley cultivars show hulled (covered) caryopses. The naked caryopsis in barley is genetically controlled by a single locus, nud. The Nud gene (the covered caryopsis allele) encodes an ethylene response factor (ERF) family transcription factor that regulates a lipid biosynthetic pathway. For functional analysis of the barley Nud gene, we produced transgenic rice expressing Nud in the developing caryopse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The composition of the surface lipids of the barley caryopsis has not yet been reported. However, Kakeda et al [ 65 ] compared thin-layer chromatographs of surface lipids extracted from the caryopses of covered and naked barley, and found little evidence of solvent-extractable compounds being present on the naked barley caryopses, despite there being a thin cuticle present on naked barley caryopses. With the findings of Taketa et al [ 18 ] that the cementing material could be dyed by Sudan Black dye, this indicates that the cementing material itself is likely to be extractable using organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the surface lipids of the barley caryopsis has not yet been reported. However, Kakeda et al [ 65 ] compared thin-layer chromatographs of surface lipids extracted from the caryopses of covered and naked barley, and found little evidence of solvent-extractable compounds being present on the naked barley caryopses, despite there being a thin cuticle present on naked barley caryopses. With the findings of Taketa et al [ 18 ] that the cementing material could be dyed by Sudan Black dye, this indicates that the cementing material itself is likely to be extractable using organic solvents.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Duan et al (2015) utilized two barley cultivars from very different genetic backgrounds, therefore it is possible that other regulatory elements could be responsible for the observed differences. Although NUD may determine the covered or naked phenotype through causing changes in cementing layer development or composition (Taketa et al, 2008; Kakeda et al, 2011), there is no evidence among covered cultivars, that the observed differences in adhesion quality are regulated by NUD in the same way.…”
Section: Introductionmentioning
confidence: 99%
“…This is significant, as increased cuticle permeability has been implicated in adhesion or organ fusion in a range of plant species (Yephremov et al, 1999 ; Sieber et al, 2000 ; Smirnova et al, 2013 ; Yeats and Rose, 2013 ). A functional NUD gene, which encodes an ethylene responsive transcription factor, is necessary, although not sufficient, for the development of the cementing layer and a permeable pericarp cuticle (Taketa et al, 2008 ; Kakeda et al, 2011 ). Without these modifications to the pericarp cuticle, there can be no adhesion between the barley caryopsis and the barley husk, or the adhesion is critically impaired in some way.…”
Section: Introductionmentioning
confidence: 99%